2011
DOI: 10.1016/j.jacc.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Left Ventricular Stroke Volume Reserve During Clinical Dobutamine Stress Predicts Future Episodes of Pulmonary Edema

Abstract: Objective To determine if dobutamine induced abnormal stress induce changes in left ventricular (LV) stroke volume (SV) and aortic stiffness predict future pulmonary edema. Background Heightened aortic stiffness that reduces LV stroke volume during adrenergic stress may serve as a marker for future pulmonary edema (P edema). Methods We measured LVSV, ventriculo-vascular stiffness (pulse pressure/LVSVi), and aortic distensibility (AoD) at rest and during intravenous dobutamine using cardiovascular magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
3
8
1
Order By: Relevance
“…The current study enrolled subjects with an earlier stage of HFpEF, where filling pressures were closer to normal at rest and physical examination evidence of congestion was largely absent. Despite the absence of right-sided structural remodeling, RV systolic and diastolic function were significantly impaired in the HFpEF group, differences that became more evident in the setting of β-stimulation, similar to prior studies evaluating LV-systemic arterial reserve with adrenergic stimulation [9][10][11][12][13] or exercise stress. 36,37 In HFpEF subjects, tricuspid annular s′ increased with dobutamine in relation to afterload reduction from dobutamine rather than an increase in contractility, which would manifest by an upward shift in the s′ versus PA pressure relationship.…”
Section: Rv Dysfunction and Rv-pa Coupling In Hfpefsupporting
confidence: 76%
“…The current study enrolled subjects with an earlier stage of HFpEF, where filling pressures were closer to normal at rest and physical examination evidence of congestion was largely absent. Despite the absence of right-sided structural remodeling, RV systolic and diastolic function were significantly impaired in the HFpEF group, differences that became more evident in the setting of β-stimulation, similar to prior studies evaluating LV-systemic arterial reserve with adrenergic stimulation [9][10][11][12][13] or exercise stress. 36,37 In HFpEF subjects, tricuspid annular s′ increased with dobutamine in relation to afterload reduction from dobutamine rather than an increase in contractility, which would manifest by an upward shift in the s′ versus PA pressure relationship.…”
Section: Rv Dysfunction and Rv-pa Coupling In Hfpefsupporting
confidence: 76%
“…The resting CV stiffness and mobility scores identified in the participants in this study are similar to those reported previously in other populations of elderly individuals (44,45). With regard to cardiac metrics, women exhibited a higher LV ejection fraction (p < .001) and CV stiffness (p = .01).…”
Section: Discussionsupporting
confidence: 86%
“…Several demographic features of the study participants including body mass index, medical history, and CV medication use were similar to those found in other studies evaluating middle-aged and older adults both at risk for or with a diagnosis of compensated CHF (5,(44)(45)(46)(47)(48). There were, however, some differences in our population of 445 individuals relative to these other previously studied populations.…”
Section: Discussionsupporting
confidence: 75%
“…Further, HFpEF is characterized by dramatic deficits in systolic reserve capacity during exercise 7, 14, 16 or β-adrenergic stimulation 17 and impaired systolic reserve is associated with reduction in overall exercise capacity, HF symptom severity and incident pulmonary edema 7, 18 .…”
Section: Hfpef Pathophysiologymentioning
confidence: 99%